The prevalence, patterns, and antifungal drug resistance of bloodstream infection-causing fungi in Sichuan Province, China (2019–2023): a retrospective observational study using national monitoring data - Deng, Jin; Liu, Ya; Shu, Ling; Zhou, Dan; Xie, Yi; Ma, Ying; Kang, Mei (Frontiers in Microbiology, 2025)
BackgroundThe rising global burden of invasive fungal infections and the growing issue of antifungal resistance present critical public health threats. By using multicenter surveillance data from Sichuan Province, we conducted the largest five-year study on fungemia to date. Our objective was to gain insights into regional differences in the distribution and resistance patterns of fungal pathogens.MethodsWe performed a retrospective analysis of fungal bloodstream infections (BSIs) from 31 hospitals (2019–2023). Integrated clinical and laboratory data were analyzed using WHONET 5.6 to assess resistance patterns, and Microsoft Excel (with PivotTable functionality) was used to analyze epidemiological trends.ResultsAnnual fungal isolations increased steadily over the study period. Candida species accounted for 88.7% (1,805/2,034) of the bloodstream isolates, with C. albicans being the most common (38.4%, 694/1,805). The majority of patients were men (58.6%, 1,191/2,034) and aged 46 years or older (80.0%, 1,627/2,034). Intensive care unit (ICU) cases accounted for 36.8% (748/2,034) of the total. C. albicans showed the highest fluconazole susceptibility (91.2%, 633/694). Both C. albicans and the C. parapsilosis complex maintained >80% voriconazole susceptibility, followed by the voriconazole wild-type C. glabrata complex (69.3%). C. tropicalis exhibited high resistance to fluconazole (36.2%, 21/58) and voriconazole (34.8%, 20/58). Cryptococcus spp. displayed non-wild-type rates to amphotericin B (8.7%), flucytosine (5.8%), fluconazole (8.7%), voriconazole (8.0%), and itraconazole (4.1%). Different hospital types isolated varying fungal species. While C. albicans was the predominant species in 83.9% (26/31) of the hospitals, pediatric specialty centers exhibited distinct microbiological profiles, showing the highest isolation rates of the C. parapsilosis complex (χ2 = 18.34, p = 0.002).ConclusionOur research conducted across several centers, revealed significant geographic variations in the spread of fungal diseases and antifungal resistance. It is important to understand local epidemiology to guide antifungal therapy and enhance stewardship programs.